Institutional Religious Freedom in Full: What the Liberty of Religious Organizations Really Is and Why It Is an “Essential Service” to the Common Good - Shah, Timothy Samuel (Religions, 2021)
Should the freedom of churches and other religious institutions come down to little more than a grudging recognition that “what happens in the church, stays in the church”? In this article, I provide a more robust definition of what I call institutional religious freedom than a crabbed and merely negative understanding. In addition, I also go beyond a libertarian-style defense of institutional religious freedom as the ecclesiastical equivalent of the “right to be left alone” by suggesting a multitude of reasons why institutional religious freedom in a robust form deserves robust protection. Especially amidst exigent challenges such as the global COVID-19 pandemic, an anemic appeal to an ecclesiastical version of negative liberty on merely jurisdictional grounds will not be enough to defend religious organizations from an increasingly strong temptation and tendency on the part of political authorities—often acting on the basis of understandable intentions—to subject such organizations to sweeping interference even in the most internal matters. In contrast, the article offers an articulation of why both the internal and external freedoms of religious institutions require maximum deference if they are to offer their indispensable contributions—indeed, their “essential services”—to the shared public good in the United States and other countries throughout the world. Underscoring the external and public dimensions of institutional religious freedom, the article follows the work of law and religion scholar W. Cole Durham in that it analytically disaggregates the freedom of religious institutions into three indispensable components: “substantive”, or the right of self-definition; “vertical”, or the right of self-governance; and “horizontal”, or the right of self-directed outward expression and action.